Level of resourcefulness and depressive symptoms after percutaneous coronary intervention： a longitudinal study - Bai Tiejuan; Shen Xiaojun; Chen Fangying; Liang Jie; Zhou Xian; Wang Jianhui (Sichuan jingshen weisheng)
BackgroundPatients after percutaneous coronary intervention （PCI） are prone to experience depression， which has been shown to significantly affect patients' quality of recovery in postoperative period. Resourcefulness plays an important role between stress and depression， yet there is insufficient research evidence on the predictive effect of intellectual resourcefulness levels on depressive symptoms among patients undergoing PCI.ObjectiveTo investigate the cross-lagged effect between level of resourcefulness and depressive symptoms among patients after PCI， so as to provide references for alleviating depressive symptoms in patients after PCI.MethodsA total of 363 patients who had undergone PCI in Tangshan Gongren Hospital from September to December 2019 were selected using random sampling technique. All participants were subjected to complete Chinese Resourcefulness Scale （CRS） and Chinese version of Cardiac Depression Scale （C-CDS） at both baseline and two years after PCI. A structural equation model was constructed to determine the cross-lagged effect between the level of resourcefulness and depressive symptoms in patients.ResultsMale patients scored higher on CRS （t=-19.871， P<0.01） and lower on C-CDS （t=25.557， P<0.01） after two years of PCI compared with female patients after PCI. Correlation analysis indicated that the baseline CRS score was positively correlated with two years after PCI CRS score （r=0.550， P<0.01）， C-CDS score of baseline was positively correlated with two years after PCI C-CDS score （r=0.524， P<0.01）， baseline CRS score was negatively correlated with C-CDS scores at both baseline （r=-0.717， P<0.01） and two years after PCI （r=-0.472， P<0.01）， and two years after PCI， CRS score was negatively correlation with C-CDS score （r=-0.618， P<0.01）. The cross-lagged analysis revealed that baseline CRS score significantly predicted CRS score of two years after PCI （β=0.382， P<0.01） and C-CDS score of two years after PCI （β=-0.200， P<0.01）. Baseline C-CDS score significantly predicted C-CDS score of two years after PCI （β=0.381， P<0.01） and CRS score of two years after PCI （β=-0.235， P<0.01）. There was a reciprocal relationship between baseline CRS score and baseline C-CDS score （β=-0.717， P<0.01）.ConclusionThe established cross-lagged model yields the presence of a reciprocal prediction of level of resourcefulness and depressive symptoms measured in patients at two time points. The higher the baseline level of resourcefulness， the lighter the depressive symptoms experienced by patients two years after PCI surgery.The more severe the baseline depressive symptoms， the lower the patients' level of resourcefulness two years after PCI surgery.［Funded by Project of Hebei Provincial Department of Science and Technology （number， 182777154）］